Hydrogen in engineering metallic materials : from atomic-level interactions to mechanical properties - Gavrili︠u︡k, V. G.; Shyvaniuk, V. M.; Teus, S. M. (Springer, 2022)
This book analyzes the effect of hydrogen on the atomic-level interactions in metals, detailing the corresponding changes in the physical properties of crystal lattice defects, diffusion, and phase transformations in metallic materials as a result of hydrogen loading. It presents a novel derivation of the structure of stacking faults, the mobility of dislocations, and short-range atomic order in hydrogen-infused metallic alloys based on the change in the concentration of free electrons. It reviews the current hypotheses behind hydrogen embrittlement of iron-, nickel, and titanium-based alloys, focusing on the phenomenon of hydrogen-enhanced localized plasticity and taking into account inherent atomic states in the alloys and other effects due to hydrogen loading. Finally, the book analyzes the use of hydrogen as an interim alloying element in the technological processing of titanium alloys, discussing the necessary preconditions for hydrogen-enhanced plasticity of metals. This book is an excellent resource for graduate students, academic researchers, and practicing engineers involved in the development of advanced hydrogen-resistant metallic materials.
Keywords: Metals -- Hydrogen embrittlement.; Alloys -- Metallurgy.; elektronické knihy; electronic books